Reconstrucción del sistema consonántico del protoyumano de California y Delta del Colorado - Gil Burgoin, Carlos Ivanhoe (El Colegio de México, A.C., 2015)
This paper presents a partial reconstruction of the inventory of phonological segments of Proto-Deltacalifornian, i.e., the hypothetical common ancestor of the languages of the Delta-California branch of the Yuman family. It is concerned with the consonantal segments of the protolanguage, based on a revised version of the comparative method. In addition to formulating a protosystem of consonants, the comparison between three languages of this Yuman sub-group suggests the necessity to reconsider the kind and degree of relationship among their members. Original received: 2014/05/15Review sent to author: 2014/07/04Accepted: 2014/08/01 .